Socioeconomic status biases among children and adolescents: The role of school diversity and teacher beliefs in Nepal. Issue 5 (25th May 2022) - Grütter, Jeanine; Dhakal, Sandesh; Killen, Melanie
Abstract: Investigating socioeconomic status (SES) biases, Nepalese children and adolescents ( N = 605, 52% girls, M age = 13.21, SD age = 1.74) attending schools that varied by SES composition were asked to anticipate whether a peer would include a high or low SES character as a math partner. Novel findings were that students attending mixed SES schools were more likely to expect inclusion of a low SES character than were students attending high SES schools. With age, high SES participants attending mixed SES schools increasingly expected the inclusion of the low SES character. Moreover, teachers' democratic beliefs in high SES schools predicted inclusive expectations. Teacher beliefs and school diversity play a significant role for fostering students' inclusivity in educational contexts.